Flexydry rack - Nasarudin, Jasmeen Emira; Mohd Hamami, Mohd Ghazali (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Clothes racks are widely used globally for air-drying laundry, especially for clothes that cannot be dried in a dryer machine. Hanging clothes racks are commonly used by those who live in apartment style houses. However, due to the minimum hanging space provided, the amount of clothes that can be dried at one time is small, which may result in difficulty for individuals living in an apartment. Therefore, the primary objective of this project is to design a flexible drying rack that can offer maximum versatility, functionality, and space efficiency. The methodologies used in this project are requirements analysis and material selection. This project will be using the concept of expansion and compression. By using this concept and mechanism, individuals will be able to dry more clothes at one time.